Smart spaces and next generation wired/wireless networking 9th international conference, NEW2AN 2009 and Second Conference on Smart Spaces, ruSMART 2009, St. Petersburg, Russia, September 15-18, 2009 : proceedings - NEW2AN 2009 (Lecture notes in computer science, 2009)
This book constitutes the refereed proceedings of the 9th International Conference on Next Generation Teletraffic and Wired/Wireless Advanced Networking, NEW2AN 2009, held in conjunction with the Second Conference on Smart Spaces, ruSMART 2009 in St. Petersburg, Russia, in September 2009. The 32 revised full papers presented were carefully reviewed and selected from a total of 82 submissions. The NEW2AN papers are organized in topical sections on teletraffic issues; traffic measurements, modeling, and control; peer-to-peer systems; security issues; wireless networks: ad hoc and mesh; and wireless networks: capacity and mobility. The ruSMART papers start with an invited talk followed by 10 papers on smart spaces. ruSMART -- ITU G.hn concept and home automation -- Extending context spaces theory by predicting run-time context -- Cross-domain interoperability: a case study -- A topology based approach for context-awareness in smart environments -- Anonymous agent coordination in smart spaces: state-of-the-art -- On-the-fly situation composition within smart spaces -- Empower mobile workspaces by wireless networks and wearable computing -- Multimodal interaction with intelligent meeting room facilities from inside and outside -- Ubi-Check: a pervasive integrity checking system --Towards a lightweight security solution for user-friendly management of distributed sensor networks -- Cross-site management of user online attributes -- NEW2AN -- Analysis and optimization of aggregation in a reconfigurable optical ADD/DROP Multiplexer -- Teletraffic capacity performance of WDM/DS-OCDMA passive optical network -- Estimation of GoS parameters in intelligent network -- Multi-skill call center as a grading from “old” telephony -- A real-time algorithm for skype traffic detection and classification -- HTTP traffic measurements on access networks, analysis of results and simulation -- The video streaming monitoring in the next generation networks -- The Poisson cluster process runs as a model for the internet traffic -- Proactive peer-to-peer traffic control when delivering large amounts of content within a large-scale organization -- ISP-driven managed P2P framework for effective real-time IPTV service -- Fault-tolerant architecture for peer to peer network management systems -- Public key signatures and lightweight security solutions in a wireless environment -- On the operational security assurance evaluation of networked it systems -- Trust management using networks of volunteers in ubiquitous computing environments. A fast and efficient handover authentication achieving conditional privacy IN V2I networks -- Robust and efficient routing in wireless mesh networks with unreliable nodes -- Video compression for wireless transmission: reducing the power consumption of the WPAN hi-speed systems -- Link stability-aware ad hoc routing protocol with multiple sampling rates – A quality of service based mobility management in heterogenous wireless networks -- A novel cooperative relaying scheme for next generation wireless networks -- Frequency allocation scheme to maximize cell capacity in a cellular system with cooperative relay -- Achieving secondary capacity under interference from a primary base station.